Analisis Social Media Marketing Dan Influencer Marketing Terhadap Keputusan Pembelian Skincare - Odilia Eva Renata Palbeno; Jelita Shintia Rani (STKIP MAJENANG, 2023)
This study aims to analyse the effect of Social Media Marketing and Influencer Marketing on purchasing decisions for skincare products. Using a qualitative research method through a literature review, this study evaluated the effectiveness of both marketing strategies in influencing consumers. The results showed that Influencer Marketing has a significant influence due to its ability to build trust and emotional connection with the audience. In contrast, Social Media Marketing does not always have a significant impact, except on platforms like TikTok that utilise creative and interactive content. This research emphasises the importance of marketing strategies that match the characteristics of the platform and target audience.